Sub-lethal pharmaceutical hazard tracking in adult zebrafish using untargeted LC-MS environmental metabolomics - De Sotto, Ryan B.; Medriano, Carl D.; Cho, Yunchul; Kim, Hyuk; Chung, In-Young; Seok, Kwang-Seol; Song, Kyung Guen; Hong, Seok Won; Park, Youngja; Kim, Sungpyo (ELSEVIER, 2017)
Antibiotics in the aquatic environment are dispersed through anthropogenic activities at low concentrations. Despite their sub lethal concentration, these biologically active compounds may still have adverse effects to non-target species. This study examined the response of adult zebrafish to 0.1 mg/L concentration of clarithromycin, florfenicol, sulfamethazine, and their mixture using environmental metabolomics. Embryo and larvae of the fish were also used to assess fish embryo acute toxicity and behavior tests respectively. The fish embryo toxicity test did not show any inhibition of growth and development of the embryos after 96 h of exposure to the antibiotics. Changes in swimming activity were seen in 5-dpf larvae which is believed to be correlated with the length of exposure to the compounds. Meanwhile, environmental metabolomics revealed diverse metabolites and pathways that were affected after 72 h of exposure of the adult fish to sub-lethal concentration of the compounds. We found that even at low concentration of the antibiotics, behavioral and metabolic effects were still observed despite the lack of visible morphological changes. Further studies involving other aquatic organisms and bioactive compounds are encouraged to strengthen the findings presented in this novel research. (C) 2017 Elsevier B.V. All rights reserved.